Seed quality of new soybean varieties produced in South Bačka in 2011 year - Vujaković Milka; Mehandžić-Stanišić Sanja; Jakovljević Nataša; Pavlović Aleksandar; Balešević-Tubić Svetlana; Milivojević Marija; Lončarević Velimir (Journal on Processing and Energy in Agriculture, 2012)
Newly developed soybean varieties differ from each other in morphological characteristics, requirements for growing conditions and technological quality of seed. The mentioned differences affect quality of seed and its viability. The aim of this paper was to determine seed quality of new soybean varieties differing in protein and oil content, and in maturity groups. Testing of seed quality was carried out on new soybean varieties developed in the Institute of field and vegetable crops in Novi Sad (NS Zenit, NS Virtus, Galina, Valjevka, Diva, NS Maximus, Sava, Balkan, Idila, Rubin, Trijumf and Vojvođanka) in the Laboratory of agricultural expert service in Novi Sad. The following seed quality traits were determined: seed moisture content, bulk density and germination of seed. Seed moisture content determined immediately after harvest ranged from 8.5% to 12.5%, and hectoliter weight from 65.5 kg/hl to 71.3 kg/hl. Statistically significant differences were found among studied varieties. The lowest values of germination were obtained in Sava (78%) and Vojvođanka (79%), and the highest in Rubin (96%) variety, while the seed germination determined by applied cold test was slightly lower. .